Perspectives of autistic adults on the strategies that help or hinder successful conversations. (May 2022) - Silver, Kate; Parsons, Sarah
Background & aims: There is increasing recognition of the importance of challenging deficit-focused, medical model approaches to supporting autistic people in daily life, however there is a lack of inclusion of autistic perspectives to inform approaches that may empower autistic people in conversations. Methods: This multiple case study used a participatory approach to explore the conversation experiences and exchange in dyads of five autistic and five non-autistic adults over four to 12 months. The study was grounded in the perspectives of autistic people through a series of semi-structured interviews, observations, reflective conversations, and diary records. Results: The findings focus on autistic participants' existing knowledge of conversations that they reported could be useful to them, including the communication environment, and type and structure of talk. The study also helped participants to identify and use previously unrecognised metacognitive abilities (what they already knew about conversations) within naturalistic interactive contexts. Conclusions: These findings provide novel insights as to how the 'interactional expertise' of non-autistic people could be strengthened to enable the effective contribution of the voices of autistic people in everyday conversations. Implications: The identification and use of successful conversation strategies identified by autistic adults gave them a greater sense of empowerment within the conversation based on their accounts of their experiences. Understanding these strategies has valuable implications for staff training, for working with families and for learning by autistic adults.